PELATIHAN PEMBUATAN ECO-ENZIM SEBAGAI UPAYA PENGELOLAAN SAMPAH ORGANIK DI SMA NEGERI 1 SEI RAMPAH - Siregar, Rosliana; Pohan, Lisa Ariyanti; Lubis, Adilah Wirdhani (LPPM Universitas Andalas, 2025)
This activity aims to analyze the effectiveness of eco-enzyme production training as an effort to manage organic waste at SMA Negeri 1 Sei Rampah, as well as to evaluate the improvement of participants' knowledge and skills in utilizing organic waste into environmentally friendly value-added products. The activity method employed active learning through socialization, demonstration, and hands-on practice (learning by doing) conducted over 7 hours involving 30 participants consisting of 15 teachers and 15 students. The activity was carried out in four main stages: socialization on organic waste management and eco-enzyme benefits, demonstration of eco-enzyme production with a material ratio of 1:3:10 (brown sugar: organic waste: water), hands-on practice of eco-enzyme production by 6 participant groups, and evaluation using pre-test and post-test. The results showed a significant improvement in participants' understanding with an average increase of 60%, where the highest improvement was observed in eco-enzyme production skills reaching 66.6%. Participant satisfaction reached 92.6% in good to excellent categories, and all groups successfully produced eco-enzyme with good quality (average score of 3.4 out of 4.0) totaling 12 liters. The conclusion of this activity is that eco-enzyme production training proved effective in enhancing knowledge and skills in organic waste management, building environmental awareness, and has the potential to become a sustainable program that can be replicated in other schools to support zero waste movements based on school communities.